Experimental & predicative analysis of engine characteristics of various biodiesels. (1st February 2021) - Rajak, Upendra; Nashine, Prerana; Chaurasiya, Prem Kumar; Verma, Tikendra Nath; Patel, Devendra Kumar; Dwivedi, Gaurav
Highlights: Effect of compression ratio were investigated of various biodiesel blend. Addition of biodiesel with diesel stronger effect on the engine performance. Knocking tendency was improved for diesel engine with higher CRs. The highest reduction in NOX emission by 45.4% for Jatropha curcas blend. Abstract: In the present study, the combustion, performance and emission characteristics of pure diesel and diesel-biodiesel (First, Second and Third Generation Feedstocks) blend (B20) on diesel engine were investigated numerically and numerical tool was validated with the experimental results. Diesel-RK software was used to numerically investigate the combustion, performance and emission characteristics with different compression ratio (16.5, 17.5 and 18.5) and loads. According to the numerical results, engine brake torque, volumetric efficiency and smoke emission decreased and the cylinder pressure, cylinder temperature, engine knocking tendency and NOX emission increased with increase in the compression ratio for diesel-biodiesel blend (B20). The chain based Zeldovich mechanism were used to calculate NOX emission for diesel-biodiesel blend and diesel fuel. The results of B20 blend shows that there was decrease in cylinder temperature by 8.2% for Jatropha curcas, engine knocking tendency by 13.47% for rapeseed, smoke by 63.85% for jojoba oil and NOX emission by 42.2% for Jatropha curcas compared to those from diesel fuel at CR17.5 with full engine load. The NOX emission of B20 blend was higher by 17.53% for jojoba, 23.0% for karanja and 8.7% for fish oil compared to diesel fuel at CR17.5 with the full load.